GC vitamin D-binding protein gene functional genetic variants and gestational diabetes mellitus risk and prediction - Ruiqi Li; Zhihua Wang; Mengyan Xiang; Qiulian Liang; Shiya Qin; Lijie Nie; Guangying Qi; Xiangyuan Yu (Scientific Reports)
Abstract Gestational diabetes mellitus (GDM) is a pregnancy-complicated disease that poses risks to maternal and infant health. However, its etiology has not yet been elucidated. This study investigated the associations between functional genetic variants of the GC vitamin D-binding protein (GC) gene and the risk of GDM. Subsequently, a nomogram predictive model was constructed for early risk identification in GDM. After adjusting for age and pre-pregnancy BMI, rs4752 A > G (AG vs AA: adjusted OR = 1.58, 95% CI: 1.19–2.10, P = 0.001; AG/GG vs AA: adjusted OR = 1.34, 95% CI: 1.04 – 1.71, P = 0.021), rs3733359 G > A (AA vs GG: adjusted OR = 0.70, 95% CI: 0.49–0.98, P = 0.039; AA vs GG/GA: adjusted OR = 0.71, 95% CI: 0.52 – 0.97, P = 0.031), and rs7041 A > C (AC vs AA: adjusted OR = 0.73, 95% CI: 0.57 – 0.94, P = 0.015; AC/CC vs AA: adjusted OR = 0.74, 95% CI: 0.58 – 0.94, P = 0.014) were significantly associated with GDM risk. In the MDR analysis, rs7041 was identified as the best single-locus model, while the two-loci model of rs4752 and rs7041 was the best multiple-factor interaction model for GDM risk prediction. It appears that rs4752 and rs7041 may alter post-transcriptional splicing, while rs3733359 alters transcription factor binding, thereby affecting individual susceptibility to GDM. A predictive nomogram model constructed with rs4752 and clinical indicators (Age, FPG, OGTT1h, OGTT2h and HbA1c) has ideal discriminant ability with a diagnostic AUC of 0.943. These findings still need to be confirmed through larger scale studies and molecular experiments in the future.